2013
DOI: 10.1186/1741-7007-11-49
|View full text |Cite
|
Sign up to set email alerts
|

Radial glial cells play a key role in echinoderm neural regeneration

Abstract: BackgroundUnlike the mammalian central nervous system (CNS), the CNS of echinoderms is capable of fast and efficient regeneration following injury and constitutes one of the most promising model systems that can provide important insights into evolution of the cellular and molecular events involved in neural repair in deuterostomes. So far, the cellular mechanisms of neural regeneration in echinoderm remained obscure. In this study we show that radial glial cells are the main source of new cells in the regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(112 citation statements)
references
References 43 publications
10
102
0
Order By: Relevance
“…6). The brittle star radial glia is very similar to their counterparts previously described in starfish and sea cucumbers [12, 14, 17, 18]. These cells are robustly labeled by the ERG1 antibody (Figs.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…6). The brittle star radial glia is very similar to their counterparts previously described in starfish and sea cucumbers [12, 14, 17, 18]. These cells are robustly labeled by the ERG1 antibody (Figs.…”
Section: Resultssupporting
confidence: 80%
“…Fluorescent immunohistochemistry on frozen sections was performed as described elsewhere [12]. Briefly, animals were anesthetized in 0.2% chlorobutanol (Sigma) and then portions of the arm, approximately 5 segments long, were fixed in 4% paraformaldehyde prepared in 0.01 M PBS (pH 7.4) overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, it has been shown that in mammals, glial cells are also involved in the regenerative process, as in holothurians (and probably in all echinoderms), but, while in echinoderms the radial glia are active in the regeneration process (Mashanov et al 2013 ), in mammals glial cells become a factor that block the process (Shearer and Fawcett 2001 ). In early-branching vertebrates, the glial reaction is, instead, permissive of regeneration (Zukor et al 2011 ).…”
Section: Nervous System Regenerationmentioning
confidence: 97%
“…However, it is from the recent study of holothuroids that new insights have been gained (see Mashanov et al 2008Mashanov et al , 2013. After transection of the radial nerve cord (RNC) in Eupentacta fraudatrix , the RNC regenerates and reconnects in about 20 days.…”
Section: Nervous System Regenerationmentioning
confidence: 99%
See 1 more Smart Citation